Tax Compliance Among Individual Taxpayers in the Digital Era: Kepatuhan Pajak Wajib Pajak Individu di Era Digital - Avida, Nurul Hidayatul; Ernandi, Herman (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Tax compliance is vital for effective revenue collection and economic stability. Specific Background: This study explores the roles of e-filing and taxpayer knowledge in influencing compliance, highlighting tax socialization as a moderating variable. Knowledge Gap: Limited research has examined how modernization, digital tools, taxpayer knowledge, and socialization interact to shape compliance behaviors. Aims: The research investigates the impact of modernizing tax administration, e-filing implementation, and taxpayer knowledge on compliance, with tax socialization as a moderator. Results: Analysis of primary data from individual taxpayers reveals that modernization, e-filing, and tax knowledge significantly enhance compliance. Additionally, tax socialization strengthens the relationships among modernization, e-filing, and compliance, as well as between tax knowledge and compliance. Novelty: This study underscores the importance of tax socialization in improving compliance through technological advancements and taxpayer education. Implications: Findings suggest that policymakers should focus on modernizing tax administration and enhancing socialization efforts to foster better taxpayer compliance. Highlights : Modernization of tax administration significantly boosts taxpayer compliance. E-filing implementation enhances compliance levels among taxpayers. Tax socialization effectively strengthens the relationship between various compliance factors. Keywords: Tax Compliance, E-Filing,Tax Knowledge, Socialization, Modernization